Situation Report: Hungary, 23 October 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. TU Activist Elected Deputy Secretary-General of National Trade Union Council Changes in the Educational System Interim Report on the 1973 Tourist Season Closed Production System Used for Private-Plot Corn Agricultural Co-operatives Form Joint Association for Application of Closed Production System The Situation of Women in the Agricultural Co-operatives Coverage of the Middle East Conflict - III